PENGARUH GLOBALISASI EKONOMI TERHADAP REFORMASI HUKUM PERUSAHAAN DI ERA MODERN - Azwar, T. Keizerina Devi; Desiandri, Yati Sharfina; Siagian, Putri Rumondang (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Globalization has significantly transformed economic, political, legal, social, and cultural dimensions worldwide, including Indonesia as a developing country. The rapid development of information and communication technology has accelerated integration into global markets and posed both opportunities and challenges for national legal systems. This article analyzes the impact of economic globalization on corporate law reform in Indonesia using a normative legal research method with a literature review approach. The discussion highlights that globalization compels legal reform through institutional, instrumental, and cultural changes, particularly in corporate governance, investment, and intellectual property protection. Findings indicate that Indonesian corporate law must adapt to global standards while maintaining national identity and constitutional values based on Pancasila and the 1945 Constitution. Strengthening legal harmonization, ensuring legal certainty, and fostering responsive law are essential to optimize the benefits of globalization while safeguarding national economic interests.